Natural Killer Cell Degranulation Defect: A Cause for Impaired NK-Cell Cytotoxicity and Hyperinflammation in Fanconi Anemia Patients - Shabrish, Snehal; Kelkar, Madhura; Chavan, Niranjan; Desai, Mukesh; Bargir, Umair; Gupta, Maya; Mehta, Priti; Chichra, Akanksha; S, Chandrakala; Taur, Prasad; Saxena, Vinay; Vundinti, Babu Rao; et al. (Frontiers in Immunology, 2019)
Fanconi anemia (FA) is a rare inherited syndrome characterized by progressive bone marrow failure (BMF), abnormal skin pigmentation, short stature and increased cancer risk. BMF in FA is multifactorial and largely results from death of hematopoietic stem cells due to genomic instability. Also, inflammatory pathology in FA has been previously reported, however the mechanism is still not clear. In literature, decreased NK-cell count and/or impaired NK-cell activity along with other immunological abnormalities has been described in FA-patients (Myers et al. 2017). However, to the best of our knowledge, this is the first report showing defective degranulation mechanism leading to abnormal NK-cell cytotoxicity in FA-patients which may explain the development of hyperinflammatory response in these patients. This may predispose some patients to develop Hemophagocytic lymphohistiocytosis (HLH) which manifests with prolonged fever, progressive cytopenias and organomegaly. Early diagnosis and initiation of immunosuppressive therapy in these patients will help in better management of these patients. We also propose FA genes to be listed as a cause of familial HLH.